Ednrb−/− mice with hirschsprung disease are missing Gad2-expressing enteric neurons in the ganglionated small intestine - Bhave, Sukhada; Guyer, Richard A.; Picard, Nicole; Omer, Meredith; Hotta, Ryo; Goldstein, Allan M. (Frontiers in Cell and Developmental Biology, 2022)
Hirschsprung disease is most often characterized by aganglionosis limited to the distal colon and rectum, and mice lacking the Endothelin receptor type B (Ednrb) faithfully recapitulate this phenotype. However, despite the presence of enteric ganglia in the small intestine, both human patients and Ednrb-/- mice suffer from dysmotility and altered gastrointestinal function, thus raising the possibility of enteric nervous system (ENS) abnormalities proximal to the aganglionic region. We undertook the present study to determine whether abnormalities with the ENS in ganglionated regions may account for abnormal gastrointestinal function. We performed single-cell RNA sequencing on ENS cells from the small intestine of Ednrb-/- mice and compared the results to a published single-cell dataset. Our results identified a missing population of neurons marked by the enzyme Gad2, which catalyzes the production of γ-Aminobutyric acid (GABA), in the small intestine of Ednrb-/- animals. This result was confirmed by immunostaining enteric ganglia from Ednrb-/- mice and their wild-type littermates. These data show for the first time that ganglionated regions of the Hirschsprung gut lack a neuronal subpopulation, which may explain the persistent gastrointestinal dysfunction after surgical correction of Hirschsprung disease.